2020
DOI: 10.3390/ijgi9040276
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Machine Learning Models and Hybrid Geostatistical Methods Using Environmental and Soil Covariates for Soil pH Prediction

Abstract: In the current paper we assess different machine learning (ML) models and hybrid geostatistical methods in the prediction of soil pH using digital elevation model derivates (environmental covariates) and co-located soil parameters (soil covariates). The study was located in the area of Grevena, Greece, where 266 disturbed soil samples were collected from randomly selected locations and analyzed in the laboratory of the Soil and Water Resources Institute. The different models that were assessed were random fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
1
9
1
Order By: Relevance
“…Random forests, on the other hand, not only incorporate randomization and bootstrapping into the construction of individual Categorization and Regression trees, but also aggregate the output of many individual trees. These characteristics are thought to counter overfitting and generally improve accuracy [22,24,29,[63][64][65][66][67]. The current study disagrees with these findings in the context of soil pH prediction.…”
Section: Cart Vs Random Forest Modelscontrasting
confidence: 94%
“…Random forests, on the other hand, not only incorporate randomization and bootstrapping into the construction of individual Categorization and Regression trees, but also aggregate the output of many individual trees. These characteristics are thought to counter overfitting and generally improve accuracy [22,24,29,[63][64][65][66][67]. The current study disagrees with these findings in the context of soil pH prediction.…”
Section: Cart Vs Random Forest Modelscontrasting
confidence: 94%
“…Comparing RF and CB with RF-OK and CB-OK predictions suggests that OK, combined with the RF and CB method, increases R 2 value by 11 to 23% in the SOCS prediction process, respectively. The hybrid methods are combined to improve the accuracy of spatial modeling predictions by other researchers (Keskin and Grunwald., 2018;Hengl et al, 2018;Tziachris et al, 2020). Other researchers (Kumar et al, 2012;Mirzaee et al, 2016;Song et al, 2017) also believed when machine learning models are combined with geostatistical methods; prediction accuracy is increased.…”
Section: Evaluation Of Machine Learning Modelsmentioning
confidence: 99%
“…However, this finding was not supported by Hengl et al (2017) who reported that estimated R 2 using XGBoost was lower for coarse fragments and soil pH compared with RF. Tziachris et al (2020) have also found that both the XGBoost and RF models presented the best results in the prediction of soil pH. Contrary to that highlighted by Chen et al (2022), the model performances did not decrease at deeper depth intervals in terms of SOC and SOCD.…”
Section: Resultsmentioning
confidence: 90%